A Case of Adult Onset Neuronal Intranuclear Inclusion Disease - Xu, Mingyuan; Wang, Jianzhong; Cha, Dazhen; Lin, Pengxin; Zheng, Zhixiong (Archives of Clinical and Medical Case Reports, 2019)
In this case of adult onset neuronal intranuclear inclusion disease (NIID), we will explore the clinical and pathological features of NIID as well as its medical imaging and histological features. The patient presented with tremor, cognitive impairment, and paroxysmal disturbance of consciousness. Diffusion-weighted imaging of cranial magnetic resonance showed high signal intensity of ribbon-like distribution at corticomedullary junction. Additionally, fibloblasts, vascular endothelial cells, and intranuclear inclusions were found on histological specimens of skin biopsy. This case suggests adult onset NIID is a disease of chronic neurological degeneration with high heterogeneity, which can be diagnosed by characteristic MRI DW1 ribbon-like high signal and eosinophilic intranuclear inclusions under electron microscopy.